What is covered by water fees, prices and costs? Examples of water policies in Turkey - Demir H.; Zahir Erkan A.; Karaca Bilgen G. (Dialogues on Mediterranean water challenges: Rational water use, water price versus value and lessons learned from the European Water Framework Directive, 2011)
The paper discusses what is understood as water price in Turkey, the components it comprises of, the methods of pricing and the advantages and disadvantages of these methods. The methods used for pricing drinking and irrigation water in Turkey are explained with examples. The structure of financing, construction, operation and maintenance is described. The question is raised whether the price for water should always cover all the costs. International organizations promote full cost recovery, but the paper demonstrates that economic, social and geographic conditions should be taken into account when setting the price. Full cost recovery can severely hinder public access to clean drinking water, specifically for the poor, because the water price may be too high compared to their income. In irrigated agriculture it can lead to the abandonment of irrigation when the water is too expensive compared to the value of the crops produced. Therefore the use of a socio-economical development index is proposed. This index helps in determining what share of the full costs can reasonably be included in the price. In addition the price may include a stimulus for water saving by using tiered pricing: the price increases with the amount of water used.
3. MELIA Workshop Water Value Impacts on the Mediterranean Water Policies, 2009/03/21-23, Istanbul (Turkey); 4. MELIA Workshop Benchmarking Exercise and Recommendations on the Application of the Water Framework Directive, 2010/03/21-26, Amman (Jordan)